2017
DOI: 10.35248/2684-1320.17.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Carpal Tunnel Syndrome in Cavanagh Syndrome: A Literature Review and Proposed Electro Physiologic Protocol

Abstract: Objective: To summarize the literature on the electrophysiology of Cavanagh Syndrome (CS), to present a clinical application and to propose an updated electrophysiologic protocol. Methods:A systematic literature search for CS was carried out and a clinical application is presented.Results: CS is characterized by congenital thenar hypoplasia and can be associated with other regional muscular and vascular anomalies. The main electrophysiologic abnormality in patients with CS is a reduced amplitude median compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Due to rarity of CTH, there are no large series of cases discussing the incidence of CTS in CTH. Kumbhare ( Kumbhare et al, 2017 ), reported a case of Cavanagh syndrome with extensive literature survey; all reported cases with Cavanagh syndrome presented with thenar muscle weakness, but mostly without significant pain or paresthesia. They surmised that in Cavanagh syndrome without co-morbid carpal tunnel syndrome, the APB and or OP was absent in more than 80% leading to absent or low amplitude CMAP over the thenar area.…”
Section: Discussionmentioning
confidence: 99%
“…Due to rarity of CTH, there are no large series of cases discussing the incidence of CTS in CTH. Kumbhare ( Kumbhare et al, 2017 ), reported a case of Cavanagh syndrome with extensive literature survey; all reported cases with Cavanagh syndrome presented with thenar muscle weakness, but mostly without significant pain or paresthesia. They surmised that in Cavanagh syndrome without co-morbid carpal tunnel syndrome, the APB and or OP was absent in more than 80% leading to absent or low amplitude CMAP over the thenar area.…”
Section: Discussionmentioning
confidence: 99%